1996
DOI: 10.1111/j.1600-0838.1996.tb00090.x
|View full text |Cite
|
Sign up to set email alerts
|

Cryotherapy in sports medicine

Abstract: The use of cryotherapy, i.e. the application of cold for the treatment of injury or disease, is widespread in sports medicine today. It is an established method when treating acute soft tissue injuries, but there is a discrepancy between the scientific basis for cryotherapy and clinical studies. Various methods such as ice packs, ice towels, ice massage, gel packs, refrigerant gases and inflatable splints can be used. Cold is also used to reduce the recovery time as part of the rehabilitation programme both af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
197
1
16

Year Published

2000
2000
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 306 publications
(227 citation statements)
references
References 49 publications
4
197
1
16
Order By: Relevance
“…Once the spindle discharge has decreased, the interference from this stimulus, in relation to muscle tension, consequently reduces. This finding corroborates previous studies that demonstrated that muscle relaxation may be obtained through applying cryotherapy and suggested that the decrease in tension was the result from a reduced frequency of discharges from the muscle spindles 9,16 .…”
Section: Acute Effectssupporting
confidence: 82%
See 1 more Smart Citation
“…Once the spindle discharge has decreased, the interference from this stimulus, in relation to muscle tension, consequently reduces. This finding corroborates previous studies that demonstrated that muscle relaxation may be obtained through applying cryotherapy and suggested that the decrease in tension was the result from a reduced frequency of discharges from the muscle spindles 9,16 .…”
Section: Acute Effectssupporting
confidence: 82%
“…A variety of studies have proven the capacity of applications of ice with this aim: this causes a reduction in the nerve conduction speed and consequently gives rise to less feeling of pain and lower spindle activity [9][10][11] . However, the study by Knight 10 indicated that, in addition to these effects, cooling caused an increase in tissue stiffness and consequently reduced the tissue viscoelasticity.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the increase in H-reflex amplitude, we observed an increase in the H-reflex latency, caused by nerve conduction velocity reduction due to cooling 16,37,38 . Similar results were found by Dewhurst et al 39 , who assessed the H-reflex after cooling in a sample of 10 young and 10 elderly women.…”
Section: Cryotherapymentioning
confidence: 83%
“…Cryotherapy is considered a therapeutic resource of temporarily reducing spasticity symptoms. It consists of lowering the stretch sensitivity of neuromuscular spindles by reducing intrafusial fiber activity in the gamma system (decreasing nerve conduction velocity) 8,16 . The TENS mechanisms of action are based on the hypothesis that it provokes an additional sensory input in the central nervous system (CNS), causing presynaptic inhibition of the suprasegmental pathways 17 .…”
Section: Introductionmentioning
confidence: 99%
“…Heat and cold therapy are well recognised modalities in the treatment of acute musculoskeletal injuries (Swenson et al, 1996) and have been recently utilised as recovery strategies among athletes to improve sport/training performances (Ihsan et al, 2013a;Wilcock et al, 2006). Moreover, there is emerging evidence highlighting the potential of these modalities to enhance mitochondrial adaptations either independently or in response to training.…”
Section: Introductionmentioning
confidence: 99%